The Diversity of Enterprise Modeling – a Taxonomy for Enterprise Modeling Actions - Seigerroth, Ulf (Complex Systems Informatics and Modeling Quarterly, 2015)
Both researchers and practitioners have recognized the need for developed knowledge about enterprise modeling. Therefore it is necessary to increase the understanding of various actions that are performed during enterprise modeling, their meaning, and their diversity. This paper proposes a taxonomy with a conceptual structure in two dimensions (hierarchy and process) that could be used to increase the knowledge about enterprise modeling actions. The taxonomy introduces a terminology that enables a better understanding of the modeling actions for a clear purpose. One important aspect of the taxonomy is to create visibility and traceability of decisions made during enterprise modeling activities. These modeling decisions have previously been of a more tacit nature and the taxonomy is supposed to make the rationale behind different modeling decisions explicit and understandable.